(untitled) - Allen, G. C. (New York, 1940)
The purpose of this study is to examine the present condition of Japanese industry and to estimate the probable future line of development. The study is primarily concerned with the results of the impact of the presen Sino-Japanese war on Japan's industrial structure.
Keywords: Nhật Bản,Japan; Điều kiện kinh tế,Economic conditions; 1918-1945,1918-1945